1998
DOI: 10.1109/66.670155
|View full text |Cite
|
Sign up to set email alerts
|

Harp test structure to electrically determine size distributions of killer defects

Abstract: To improve accuracy of electrically based measurements of defect densities and defect size distributions, we present a novel Harp Test Structure (HTS). There, horizontal and vertical parallel lines will be placed inside a given boundary pad frame without using any additional active semiconductor devices. The enhanced two-dimensional (2D) permutation sequence provides that all neighborhood relationships of adjacent test structure lines are unique. This is the key to disentangle even multiple faults detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The parameter depends on the environment of the LSI fabrication line. The data reported from various fabricators shows a value of about 3 [3], [5]. In the case , (6) becomes simpler as (7) This indicates that the effective critical area does not change by chip shrink, which agrees with the results reported in a special case with parallel stripe patterns [6].…”
Section: A Yield Modelsupporting
confidence: 82%
See 2 more Smart Citations
“…The parameter depends on the environment of the LSI fabrication line. The data reported from various fabricators shows a value of about 3 [3], [5]. In the case , (6) becomes simpler as (7) This indicates that the effective critical area does not change by chip shrink, which agrees with the results reported in a special case with parallel stripe patterns [6].…”
Section: A Yield Modelsupporting
confidence: 82%
“…Then, is given as (4) where . On the other hand, if the chip is enlarged proportionally by increasing the number of transistors by a factor of will increase in proportion to for the same value and hence (5) In the case where both of the above instances occur simultaneously, the effective average number of defects on a chip is given as (6) where is the rate of the design rule shrink, is the rate of the transistor count increase and is the original effective critical area before the chip shrink and the transistor count increase. This provides a generalized formula for the effective critical area.…”
Section: A Yield Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The data in the figure is separated according to defect size, corresponding to the total defect count detected by inline defect inspection after Cu CMP of several wafers. Most reports have indicated that is inversely proportional to the second or third power of [8]- [11]. However, the shape of the distribution in Fig.…”
Section: B Overlaying Defect Data and Electrical Measurement Datamentioning
confidence: 84%
“…More than one and a half of outlines of defects resemble ellipse, which is usually modeled as a circle in the yield model, which causes the errors estimation for IC [9,10]. This paper discusses the yield model and its correlative critical area model for an elliptical defect.…”
Section: Introductionmentioning
confidence: 97%